\(12x^{6}-3x^{2}\)

\(=3x^{2}(4x^{4}-1)\)

\(=3x^{2}(2x^{2}-1)(2x^{2}+1)\)

\(=3x^{2}(\sqrt{2}x-1)(\sqrt{2}x+1)(2x^{2}+1)\)

\(=3x^{2}(4x^{4}-1)\)

\(=3x^{2}(2x^{2}-1)(2x^{2}+1)\)

\(=3x^{2}(\sqrt{2}x-1)(\sqrt{2}x+1)(2x^{2}+1)\)

Question

asked 2021-05-28

Let \(P(x)=x^{3}-3x^{2}+x-3\)

Find all the zeros of P.

Find the complete factorization of P.

Find all the zeros of P.

Find the complete factorization of P.

asked 2021-05-09

Choose the complete factorization of \(4x^{2} - 8x - 60\).

a)2(x + 3) (x - 5)

b)\(4(x^{2} - 2x - 15)\)

c)(2x + 6) (2x - 10)

d)4(x + 3) (x - 5)

a)2(x + 3) (x - 5)

b)\(4(x^{2} - 2x - 15)\)

c)(2x + 6) (2x - 10)

d)4(x + 3) (x - 5)

asked 2021-06-03

Find the complete factorization of \(P(x)= x^{4} - 2x^{3} + 5x^{2} - 8x + 4\).

asked 2021-05-13

Complete the factorization

\(2t^{2}(6t-1)+3(6t-1)\)

\(2t^{2}(6t-1)+3(6t-1)\)